Development of water-based printable piezoresistive sensors for large strain applications - Gonçalves, B. F. (2017)
Polymer based smart materials and, in particular, piezoresistive ones, are increasingly being used in a wide variety of applications ranging from automotive components to medical devices. This work reports on water-based piezoresistive polymer composites developed from thermoplastic poly(vinyl alcohol) (PVA) filled with carbon nanotubes (MWCNT) for the fabrication of high performance piezoresistive materials and sensors. PVA is a water-soluble synthetic polymer with suitable mechanical properties for the development of large strain sensors. MWCNT/PVA nanocomposites with good linearity between deformation and electrical resistance variation and with gauge factors up to 3 were achieved. Further, the materials were formulated in the form of inks for spray and screen printing of the sensors, which demonstrated a good performance for strain sensing both under laboratory tests conditions and when connected to a readout and communication system. Therefore, polymer based piezoresistive sensors were developed by a green approach and capable to be implemented by scalable printing technologies